Synergistic Effects of NOTCH/γ-Secretase Inhibition and Standard of Care Treatment Modalities in Non-small Cell Lung Cancer Cells - Sosa Iglesias, Venus; Theys, Jan; Groot, Arjan J.; Barbeau, Lydie M. O.; Lemmens, Alyssa; Yaromina, Ala; Losen, Mario; Houben, Ruud; Dubois, Ludwig; Vooijs, Marc (Frontiers in Oncology, 2018)
Background: Lung cancer is the leading cause of cancer death worldwide. More effective treatments are needed to increase durable responses and prolong patient survival. Standard of care treatment for patients with non-operable stage III-IV NSCLC is concurrent chemotherapy and radiation. An activated NOTCH signaling pathway is associated with poor outcome and treatment resistance in non-small cell lung cancer (NSCLC). NOTCH/γ-secretase inhibitors have been effective in controlling tumor growth in preclinical models but the therapeutic benefit of these inhibitors as monotherapy in patients has been limited so far. Because NOTCH signaling has been implicated in treatment resistance, we hypothesized that by combining NOTCH inhibitors with chemotherapy and radiotherapy this could result in an increased therapeutic effect. A direct comparison of the effects of NOTCH inhibition when combined with current treatment combinations for NSCLC is lacking. Methods: Using monolayer growth assays, we screened 101 FDA-approved drugs from the Cancer Therapy Evaluation Program alone, or combined with radiation, in the H1299 and H460 NSCLC cell lines to identify potent treatment interactions. Subsequently, using multicellular three-dimensional tumor spheroid assays, we tested a selection of drugs used in clinical practice for NSCLC patients, and combined these with a small molecule inhibitor, currently being tested in clinical trials, of the NOTCH pathway (BMS-906024) alone, or in combination with radiation, and measured specific spheroid growth delay (SSGD). Statistical significance was determined by one-way ANOVA with post-hoc Bonferroni correction, and synergism was assessed using two-way ANOVA. Results: Monolayer assays in H1299 and H460 suggest that 21 vs. 5% were synergistic, and 17 vs. 11% were additive chemoradiation interactions, respectively. In H1299 tumor spheroids, significant SSGD was obtained for cisplatin, etoposide, and crizotinib, which increased significantly after the addition of the NOTCH inhibitor BMS-906024 (but not for paclitaxel and pemetrexed), and especially in triple combination with radiation. Synergistic interactions were observed when BMS-906024 was combined with chemoradiation (cisplatin, paclitaxel, docetaxel, and crizotinib). Similar results were observed for H460 spheroids using paclitaxel or crizotinib in dual combination treatment with NOTCH inhibition and triple with radiation. Conclusions: Our findings point to novel synergistic combinations of NOTCH inhibition and chemoradiation that should be tested in NSCLC in vivo models for their ability to achieve an improved therapeutic ratio.